Consumer Communities and Second-Hand Clothing Swaps as Drivers of Circularity in Fashion Industry - Győri, Zsuzsanna; Szegedi, Krisztina; Oravecz, Titanilla (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The transition to a circular economy in the fashion industry can provide answers to environmental problems such as waste production or water usage, while also contributing to the solution of social problems such as child labour and psychological problems arising from overconsumption, thereby contributing significantly to the achievement of Sustainable Development Goals (SDGs). Circular economy is mostly interpreted as an umbrella term that can define highly contradictory ideas of sustainable development especially regarding business actors. Thus, both in theory and practice, it is very important to involve various actors, including consumers, not just deal with corporate solutions. The basic assumption is that circular economy should be based on social and economic structures. That is why our research examines second-hand clothing swaps and other consumer community solutions and the potentials for linking them to corporate initiatives, giving greater opportunities for truly effective circular solutions and the cooperation of different stakeholders.